Multimedia Learning Material Impact on a Bootcamp Training Program at Merdeka Campus - Heriyanni, Eileen; Qomariyah, Nunung Nurul (Engineering, MAthematics and Computer Science Journal (EMACS), 2024)
The use of multimedia in teaching and learning activities has been a practice that has been going on for a long time, especially since COVID-19. Teaching and learning activities using multimedia seems more interesting and able to increase student’s learning interest. This research highlights the use of multimedia material in technical bootcamp training program for non-technical background participants who are studying data analytics in certified independent studies program at Merdeka Campus. Data obtained by interview and discussion with Subject Matter Expert (SME) and study literature with Republic Indonesia National Standards for Higher Education, Outcome Based Education (OBE), Instructional System Design (ISD), Bloom Taxonomy, and Kirkpatrick Model to develop the program curriculum which later analyzed and processed to become the basis for multimedia material development. The evaluation of multimedia material implementation is assessed with a questionnaire which measures participants' perception of the multimedia material used in bootcamp activity to improve their knowledge and skill while studying data analytics. The conclusion of this research is to prove the impact of using multimedia material on the teaching and learning process through the results of participants’ average passing score which reached at 78.01 and the engagement of participants' commitment to the program which concluded in graduated percentage, reached at 73.33%.